Spindle cell tumours of the female genital tract - Olaofe, Olaejirinde O.; Okongwu, Chigozie C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Our aim is to describe the clinicopathology features of spindle cell tumors of the female genital tract seen in our hospital and to compare the findings with what is seen in other parts of the world. Methods: We conducted a cross-sectional study of all spindle cell tumors diagnosed in the department of Morbid Anatomy and Forensic medicine of Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria from January 1, 2017, to December 31, 2022. Results: Leiomyoma was the most common spindle cell tumour seen. Only 570 cases met the inclusion criteria. Only one nodule was removed in 130 cases (22%) while greater than one nodule was excised in 432 cases (75.8%). The mean age of patients was 40.77 years while the age range was 19-79 years. About three-quarters of leiomyomas are removed in the age-group 31-50. There was no correlation between the number of nodules removed and the age of the patient. The next second most common spindle cell tumor seen was malignant mixed mullerian tumour. Eleven cases were seen in the study period, The average age was 57.7 years. The age range of cases was 27-72 years. Conclusions: Our study supports the general observation that leiomyomas commonly cause symptoms in the reproductive age group and that most patients with leiomyoma frequently have more than one nodule. Our study further reinforces the widely established knowledge that MMMT is found in older post-menopausal women and can occasionally be seen in younger pre-menopausal women.